ANALISIS INDEKS KEPUASAAN MASYARAKAT TERHADAP KEBERADAAN PASAR TRADISIONAL DI KABUPATEN PEKALONGAN - Dwi Susilo; Choliq Sabana (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2013)
Research with the title  : Satisfaction Index Analysis Society Against Traditional Market Presence In the  District  Pekalongan  has  a  purpose  to  know  the  value  of  Community  Satisfaction  Index  of  the existence  of  Traditional  Markets  in  District  Pekalongan.  This  study  was  conducted  based  on  the population of traditional markets in the region Pekalongan 9 units, respondents were randomly selected based on the number of merchants who sell and market visitors in every market studied using stratified random sampling technique of sampling by looking at the proportion of each place. The respondents include: a. Traders are user kiosks, los, and lapak.dan b. Visitor market. Indicators of market service user community satisfaction is measured by the decree PAN Number: Kep/25/M.PAN/2/2004 general guidance on public satisfaction indexing services unit of government agencies. The results showed that the results of the calculation of the index of satisfaction with the services of traditional markets in the District 9 Pekalongan show that the perception of the average trader satisfaction with services market by  70.84%  or  the  quality  of  service  B  (good).  And  the  results  of  the  calculation  of  the  index  of satisfaction  with  the  services  of  traditional  markets  in  the  District  9  Pekalongan  show  that  the perception  of  the  average  appraisal  of  satisfaction  with  the  service  market  of  67.83  in  the  quality  of service B (good)The Keywords: Traditional Markets, Services and Community Satisfaction Index